2016
DOI: 10.12659/msm.897330
|View full text |Cite
|
Sign up to set email alerts
|

Increased Plasma miRNA-30a as a Biomarker for Non-Small Cell Lung Cancer

Abstract: BackgroundMicroRNA (miRNA) is a small, non-coding RNA molecule which plays a role in the carcinogenesis and progression of cancers. Abnormal expression of miRNA in plasma has been found in some patients with malignant tumors.Material/MethodsThis study was conducted to investigate the expression of miRNA-30a in plasma of patients with non-small cell lung cancer (NSCLC). The plasma miRNA-30a in 87 patients with NSCLC, 20 patients with benign lung diseases, and 76 healthy subjects were measured by real-time PCR. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 30 publications
0
17
0
2
Order By: Relevance
“…Similar results were revealed in hepatocellular carcinoma (HCC), breast cancer, and gastric cancer [41][42][43], which suggested that miR-30a served as a tumor inhibitor. However, in non-small cell lung cancer (NSCLC) and glioma patients, plasma miR-30a was significantly overexpressed relative to the benign control group [44,45]. Our study utilized acquired data to demonstrate that miR-30a was expressed at a low level in PaCa with a pooled SEN of 0.6, SPE of 0.80 and AUC of 0.78, which could distinguish PaCa from controls.…”
Section: Discussionmentioning
confidence: 98%
“…Similar results were revealed in hepatocellular carcinoma (HCC), breast cancer, and gastric cancer [41][42][43], which suggested that miR-30a served as a tumor inhibitor. However, in non-small cell lung cancer (NSCLC) and glioma patients, plasma miR-30a was significantly overexpressed relative to the benign control group [44,45]. Our study utilized acquired data to demonstrate that miR-30a was expressed at a low level in PaCa with a pooled SEN of 0.6, SPE of 0.80 and AUC of 0.78, which could distinguish PaCa from controls.…”
Section: Discussionmentioning
confidence: 98%
“…Two other validated microarray analyses identified plasma miR-30a and serum miR-1244 as independent diagnostic markers for discriminating NSCLC from both benign lung lesion and healthy controls. MiR-30a has AUC, sensitivity, and specificity values of 0.727, 61%, and 84% for NSCLC, and 0.727, 55%, and 94% for benign lesions [65]. MiR-1244 discriminates all-stage and early-stage NSCLC patients both from healthy controls (AUC, specificity, sensitivity: 0.832, 82%, 80%, and 0.80, 54%, 100%, respectively) and from benign pulmonary nodules (0.861, 78%, 92%, and 0.848, 73%, 92%) [66].…”
Section: Mirnas As Tumor Biomarkersmentioning
confidence: 99%
“…Several studies have associated microRNAs (miRs) deregulation with ccRCC clinicopathological features, suggesting a role in tumor initiation and progression [5,7,16,17]. MiR-30a-5p, an intergenic miR (chromosome 6, 71,403,551-71,403,621 [− strand]), was suggested to play a role in cellular differentiation and development [18], but its precise role remains largely unknown [19,20]. In ccRCC, an oncosuppressor function was proposed for miR-30a-5p, since its downregulation was associated with metastasis development [5,9].…”
Section: Introductionmentioning
confidence: 99%